STRATEGI PENDIDIKAN ISLAM DALAM OPTIMALISASI PENGEMBANGAN POTENSI ANAK DI MA DARUL ‘ULUM TLOGOWUNGU PATI - Nurul Hidayati (PASCASARJANA UNISNU, 2019)
AbstractThis study describes the strategy of Islamic education in optimizing the development of children's potential in MA Darul 'Ulum Tlogowungu Pati. The results of this study concluded that efforts to recognize children's intelligence are the first steps that can be taken before starting to guide children in achieving their optimal intelligence. The main goal is that educators are able to truly understand and recognize the potential that each student has. So that it can make it easier for educators to direct and guide their students to develop the potential. Ways or strategies that educators can do to recognize the potential of their students can be done in several ways, including: observing children's daily behavior, observing how children spend their free time, and observing children when they react.Keywords: optimizing, developing children’s potential, Islamic education